The Impact of COVID-19 on The Teaching of Non-Medical Healthcare Professionals in Bangladesh: Observations and Implications From A Pilot Study - Adnan, Nihad; Haque, Mainul; Mou, Taslin Jahan; Islam, Salequl; Nahar, Shamsun; Chowdhury, Kona; Zaman, Taslima; Akter, Farhana; Sharmin, Sabrina; Nusrat, Nadia; Kabir, Rumana; Biswas, Nirmal Kanti; et al. (Bangladesh Journal of Medical Science, 2022)
Objective: At the start of the Covid-19 pandemic, educational establishments, including universities, were closed. Educators in high-income countries quickly shifted all education online, building on available infrastructures and approaches. However, there were concerns in developing countries regarding the necessary skills among students and faculty as well as financial support for equipment and the internet. Consequently, a pilot was undertaken in Bangladesh to determine the impact of Covid-19 on the non-medical education system, building on similar research with healthcare professionals. Materials and Methods: A purposively designed questionnaire was disseminated among eight non-medical healthcare educators in private and public universities in Bangladesh. Results and Discussion: Private university educators reported their universities readily adopted e-learning systems and resumed classes more quickly than public universities. Both private and public university educators shared similar challenges, including a lack of training on e-learning initially, variable internet connections, affordability of internet bundles, concerns with available devices, as well as mental stress of faculty and students. Private universities reduced their tuition fees, extended submission deadlines, and shared class recordings to address challenges. Public universities arranged student loans, established Covid-19 testing centers, and the trained students in biosafety practices and molecular tests to volunteer in testing facilities. Conclusion: Lessons learned from the pandemic emphasize introducing hybrid education systems with full technological and financial support, alongside biosafety education in the curriculum. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 731-743